Best Practice of Halal Tourism Development in Various Countries: A Literature Review - Muhamad Azami Nasri (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2023)
Over the past few years, halal tourism has experienced rapid development worldwide. Halal tourism is present as a unique tourism concept and promotes Islamic law. Halal tourism also provides an accelerator for economic growth in a country. In addition, the projected presence of Muslim tourists will reach 140 million in 2023 and 160 million in 2024. Many countries with Muslim-majority populations are competing to develop halal tourism. However, until now, Indonesia, Malaysia, and Turkey have become the most competitive countries in developing world halal tourism according to the